Information Dissemination Effects To Provision of Land for Railway Lines In Relationship with the Knowledge, Attitude and Behavior of the Land Owners in Barru Regency, South Sulawesi - Indonesia - Cangara, Hafied; Supriyadi, Ahmad; Salle, Aminuddin (Advances in Social Sciences Research Journal, 2017)
The aims of the research were to determine the effect of information dissemination of land acquisition of railways on knowledge, attitude and behavior of the land owners in Barru, and to determine the factors that affect the process of land release for railway construction in Barru. This study was conducted in Barru with quantitative approach. Population of the study were 899 land owners around the railway in Barru. Sample were 100 people selected with Slovin formula. Data were analyzed with linear regression analysis. Results of the research indicated that the influence of information dissemination conduct of the land owners through television was 3.9%, newspaper 5.8%, online media 7.8% , interpersonal communication 26.04 %, and group communication 21.5 %. Interpersonal communication had the greatest effect among the five communication channels. Factors influencing the process of land release for the railway construction in Barru were public interest, government programs, religious knowledge, the compensation value and a sense of pride the railway presence in Barru.